Pop-Up Book of Balinese Folktale I Pengangon Bebek to Enhance Cultural Literacy of Elementary School Students - I Gusti Ngurah Agung Susila Sukajaya; Luh Putu Sri Lestari (Universitas Pendidikan Ganesha, 2025)
The low cultural literacy abilities of third grade elementary school students regarding local culture are caused by limited information related to culture. The influx of foreign culture through social media can reduce interest in local culture. This research aims to produce a pop-up book on Bali I Pengangon Bebek with the topic that each component has a role in improving the cultural literacy skills of third grade elementary school students, which has been tested in terms of validity, practicality and effectiveness. This research uses qualitative and quantitative data analysis techniques using test methods, assessment scales and questionnaires. The subjects of this research involved pop-up books and 19 third grade elementary school students. The results of the research show that: (1) the printed pop-up book contains Satua Bali cultural content with the topic